2013
DOI: 10.3402/qhw.v8i0.20870
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experience of important factors in the healthcare environment in oncology care

Abstract: Background and objectiveThe aim of this study was to describe what factors of the healthcare environment are perceived as being important to patients in oncology care.DesignA qualitative design was adopted using focus group interviews.Setting and participantsThe sample was 11 patients with different cancer diagnoses in an oncology ward at a university hospital in west Sweden.ResultsAnalysis of the patients’ perceptions of the environment indicated a complex entity comprising several aspects. These came togethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
50
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 34 publications
3
50
0
8
Order By: Relevance
“…Based on their findings, Browall et al (2013) suggested that the psychosocial environment is of greater importance than the physical environment for persons with cancer. Nevertheless, according to Edvardsson et al (2006), the physical environment is an important symbol of care, and is charged with value.…”
mentioning
confidence: 99%
“…Based on their findings, Browall et al (2013) suggested that the psychosocial environment is of greater importance than the physical environment for persons with cancer. Nevertheless, according to Edvardsson et al (2006), the physical environment is an important symbol of care, and is charged with value.…”
mentioning
confidence: 99%
“…Even less attention has been paid to how the surroundings might support death and dying being understood as a meaningful experience, in line with one's own life and history. While the literature on these issues in EoL care remains limited, recent reviews and research on health care design more generally (Andritsch et al, 2013;Browall et al, 2013;Drahota et al, 2012;Salonen et al, 2013;Ulrich, 2013;Ulrich et al, 2008) found a growing body of robust studies indicating that the physical care environment can promote improved outcomes for patients (e.g. reducing stress, diminishing use of analgesics, facilitating coping, and promoting well-being), as well as staff.…”
Section: Introduction and Aimmentioning
confidence: 97%
“…Empathy is a multidimensional concept that transcends specific contexts (i.e., trait) yet is also an elicited emotion in specific situations (i.e., state) [11][12][13][14]. As such, particular circumstances may deter an inherently empathic physician from delivering patient-centered care, preferred by a majority of patients and contributing to overall patient satisfaction [15][16][17]. Physician empathy is threatened by multiple factors including work-related distress, loss of a personal sense of well-being, and the burnout phenomenon [8,10,18,19].…”
Section: Introductionmentioning
confidence: 99%